A retrospective study of biochemical parameters and outcomes of obstetric cholestasis: with and without pruritus - Nidhi Garg; Veena Ganju Malla (Barpeta Obstetrics and Gynaecological Society, 2020)
Objectives: The objective was to study the differences in the biochemical parameters and outcomes of obstetric cholestasis with and without pruritus. Methods: This retrospective hospital based study was done from July 2014 to June 2018 where 160 confirmed cases of cholestasis were included in the study. The subjects were assessed for demographic parameters, obstetric history, and liver function tests, including bile acids. Results: Pruritus was seen in 128(80%) patients. There were significantly higher levels of serum bilirubin in the patients without pruritus; other parameters were comparable. Maternal outcome parameters were comparable. All the infants born to mothers in without pruritus group and 84.38% of those born to mothers with pruritus recovered uneventfully. No stillbirths and intrauterine deaths were reported. Conclusions: Among all Obstetric cholestasis patients, pruritus was not present in 20% of patients. Patients without pruritus had significantly higher serum bilirubin, while other parameters of liver function tests were statistically comparable to cholestasis women with pruritus. The cautious management of women without pruritus resulted in uneventful deliveries and comparable outcomes with those with pruritus.